Development of the Electrical Engineering Drawing E-Module in the Department of Electrical Engineering, Jakarta State University - Nursyahied, Imam; Priyanto, Sugeng; Syahrir, Syahrir (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to develop an electronic book-based learning media to support the teaching of electrical engineering drawing in the Department of Electrical Engineering at Universitas Negeri Jakarta. Using the Research and Development (R&D) method with the Four-D model (excluding the dissemination stage), the learning media was evaluated by material experts, media experts, and tested with students.The evaluation results show that the learning media achieved an average feasibility score of 91.1% from material experts, 85% from media experts, and 87.1% from students, all categorized as